Opportunities and challenges in access to healthcare for international migrants with work-related diseases and injuries in Gulf Cooperation Council countries: A systematic literature review protocol - Weijun Yu; Aleena Dawer; Jeanetta Floyd; Nicole Saad; Jiaqin Wu; Katherine O. Robsky; Oliver Johnson; Yulia Hutsul; Dylan Ratnarajah; Bryan Shaw; Martine Etienne-Mesubi; Deus Bazira (PLoS ONE, 2025)
Introduction International labor migrants form a significant part of the global workforce, particularly in the Gulf Cooperation Council (GCC) countries, which host around 11% of the world’s migrant workforce. This high concentration presents unique challenges in healthcare access and delivery. This systematic review aims to evaluate whether international labor migrants in GCC countries have effective access to healthcare for work-related diseases and injuries and to propose evidence-based recommendations for policy and healthcare interventions. Methods We will include studies from 2013 to 2023 published in peer-reviewed journals in English or Arabic (with English abstracts) available on PubMed, Embase and CINAHL. Search strategies are developed using MeSH terms and key terms related to our study population (international labor immigrants), context (the GCC countries), and exposure (migrant status; work-related diseases and injuries). The screening process involves two stages: initial review of titles/abstracts and full-text review. Studies meeting eligibility criteria and focusing on our primary outcome (access to healthcare) will be included. Data extraction will cover study characteristics, population demographics, described exposures, outcomes measured, and key findings. Given the expected heterogeneity, narrative synthesis will be primarily used, with meta-analysis as an option. Discussion By considering both migrant workers and expatriate professionals, we provide a culturally tailored perspective. Methodological rigor is ensured through the gold standard screening process, where at least two reviewers independently screen the literature at each stage, with a senior reviewer resolving discrepancies. We will identify barriers, facilitators, and inform targeted interventions for policymakers. Our findings will support evidence-based strategies to improve healthcare access for international labor migrants in the GCC countries. Systematic review registration This systematic review protocol was registered on the international registry PROSPERO (CRD42024532851) on April 21, 2024.